P-178 Cost-effective innovations for integration of palliative care and respiratory services. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Ferguson, Claire; Burge, Geraldine; Barclay, Sue
Abstract : Background: It is recognised that chronic respiratory patients benefit from palliative care due to their burden of symptoms and risk of inappropriate medical interventions at end of life (Joshi, Joshi, & Bartter, 2012; Taylor & Murray, 2018). However, respiratory referrals to our palliative care services have remained low. Research has shown that patients and staff can equate palliative care with 'giving up' (Smallwood, Gaffrey, Gorelik et al ., 2018) when exacerbations are potentially reversible, resulting in patients dying in hospital, whilst undergoing active medical management. Aims: Understand the needs of chronic respiratory patients. Increase respiratory referrals to hospice services. Increase knowledge and skills for healthcare professionals in managing palliative respiratory patients. Methods: Using contacts from the community specialist nurses and hospital palliative care team, a quarterly meeting at the hospice was set up for interested healthcare professionals from the hospice, community and hospital involved in working with chronic respiratory patients. By sharing information on the services available and discussing complex respiratory cases, new ways of working together were identified. These included: Respiratory nurses observing consultant ward rounds at the hospice The hospital oxygen clinic being held at the hospice The Interstitial Lung Disease support group moving to the hospice Developing a respiratory breakfast club at the hospital for palliative and respiratory staff to discuss the management of hospital and community respiratory patients Hosting a regional conference on interstitial lung disease at the hospice Joint home visits with the respiratory and palliative care teams. Results: Anecdotal evidence so far has shown an increase in referrals of respiratory patients to Hospice services and these patients have benefitted from palliative care. Quantifiable data will be available by November 2018. Conclusions: It is possible to increase referrals from respiratory to palliative care without expensive or time-consuming interventions. Developing relationships and improving understanding between the teams has helped to break down barriers and led to further collaborative working.